How New Secondary School Headteachers access Coaching and Mentoring: Support Strategies for New Senior Leaders - Linda Neal (International Journal of Evidence Based Coaching and Mentoring, 2012)
This article derives from doctoral research which took a client perspective and a grounded theory approach to investigate how new secondary school headteachers use coaching and mentoring. Six newly appointed headteachers in England were interviewed three times during their first year in post. The article reports one aspect of the findings, namely how newly appointed secondary school headteachers access their coaching and mentoring support. Member checks undertaken with experienced coaches indicate that research findings could be transferable to other circumstances and sectors.